Survival rate, body size and food abundance in pure and mixed blowfly cultures - Rosa, G. S.; de Carvalho, L. R.; Godoy, WAC (Entomological Soc Southern Africa, 2004)
The influence of food abundance, larval density and interspecific interactions on the survival and body size of Chrysomya albiceps, Chrysomya megacephala and Cochliomyia macellaria was investigated in pure and mixed cultures, to determine the impact of competition and/or facultative predation on native and introduced blowfly species in South America. In mixed cultures there was complete elimination of C. megacephala and C. macellaria. Chrysomya albiceps exhibited higher survival in mixed compared to pure cultures, suggesting that predation offers more advantages than competition for food. Body size of C. albiceps was significantly affected by food scarcity in pure cultures. However, tibia size in males of all species suffered no significant variation as a function of food scarcity. The implications of these results for population dynamics of introduced and native blowfly species are discussed.
Keywords: larval density; facultative predation; Chrysomya albiceps; Chrysomya megacephala; Cochliomyia macellaria